From self-descriptions (SD) to self-recommendations (SR): Evolving Gaia-X for the future European economy - Vincent Geilenberg; Wolfgang H. Schulz; Jonathan Mize; Henrik Kleis (International Journal of Information Management Data Insights)
The European decentralized-organized data-infrastructure ecosystem Gaia-X faces the challenge of initiating, maintaining, and intensifying data exchange between data providers and data consumers in all its Gaia-X data exchange domains to contribute significantly to the future viability of the European economy. The overall success of Gaia-X would enhance the innovative power and competitiveness of European companies and reduce their dependence on American and Chinese platform companies. This paper analyzes how the Big Data era affects the design of centralized-organized and decentralized-organized platforms and applies the findings to Gaia-X. It proposes to extend the Self-Descriptions (SD) already firmly embedded in Gaia-X with so-called Self-Recommendations (SR) because, in this way, the decentralized-organized data-infrastructure ecosystem Gaia-X can better express its advantages over centralized-organized platform companies.